PELAKSANAAN PELAYANAN KEHAMILAN DI PUSKESMAS LEGOK TANGGERANG TAHUN 2022 - Rambe, Novitasari; Triyana Sari (Ebers Papyrus, 2024)
Examination of pregnancy services during pregnancy is a determinant of the quality of the well-being of the pregnant mother and fetus, because the patient will receive information that is useful for changing the patient's bad habits into good ones and will make them feel like they have received a lot of information to further maintain the quality of the pregnancy until the time of delivery. According to the World Health Organization (WHO), In 2015, complications during pregnancy and delivery caused 830 maternal fatalities for every 100,000 live births. The 2019 IDHS found that out of 100,000 live births in Indonesia, there was a maternal mortality rate (MMR) of 305. The maternal mortality rate in Tangerang city was 83 per 100,000 live births in 2016, with 239 maternal deaths. This research made use of a cross-sectional observational analytic technique. The study was done between February and April 2023, gathering medical record data from 200 pregnant women in the third trimester at the Legok District Health Centre in Tangerang.